RELEVANSI FIKIH TRADISIONAL - Desy Kristiane (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2022)
In terms of thinking and understanding, Muslims can be divided into four social ideological paradigms or groups, namely traditional, modernist, revivalist, and transformative groups. Traditional fikih has become one of the characteristics of Islamic legal thinking that has developed and still exists in Indonesia. This traditional fikih thinking is guarded and preserved in the academic world of pesantren, although it does not cover the possibility that many pesantren graduates have new thoughts by adapting to the development of problems experienced by society. This paper describes the development of fikih and the weaknesses in the relationship between traditional fikih and pesantren education, in which pesantren graduates are required to be involved in solving the problems of the nation and state. The conclusion is that the existence of traditional fikih is due to the attitude of the scholars who are careful in accepting new things because they are worried that these new things will harm people's lives.